PENGARUH KOMUNITAS - KOMUNITAS TERHADAP MINAT BELI KONSUMEN DI RESTORAN SEDERHANA BATU AJI KOTA BATAM - Moh. Thandzir; Tito Pratama; Haufi Sukmamedian; Dailami (JURNAL MANAJEMEN KULINER, 2023)
A business has its own way of achieving sales targets and the number of consumers. Apart from the method used by the restaurant itself, external factors, namely the existence of a community, also affect the restaurant in achieving its goals. Community is a collection of people in large numbers and form social groups that work together to achieve common interests or goals and occupy a certain area for quite a long time. The type of this research is the study of The Influence of Community on Consumer Purchase Interest in the Batu Aji Simple Restaurant in Batam City where at this point we know that the Batu Aji Simple Restaurant in Batam City is quite famous and crowded with visitors in the city of Batam. The sampling technique used nonprobablity sampling technique with purposive sampling with a total sample of 98 respondents. Data collection was carried out using literature studies, interviews, observations, and questionnaires. Questionnaire data were analyzed using SPSS ver 25. Data analysis techniques used simple linear regression analysis. The results of the t-test, namely the influence of the community, have a t count of 12.477. The results of this study indicate that the community has an influence on consumer buying interest at the Batu Aji Simple Restaurant in Batam City.